Increased vegetation disturbance intensity reduces soil nutrients while enhancing microbial network interactions - Gao, Boya; Xiao, Dan; Yang, Kaixun; Sun, Mingming; Luo, Shantong; Zhang, Wei; Wang, Kelin (Frontiers in Microbiology, 2025)
Introduction and methodsVegetation disturbance intensity serves as a critical determinant of changes in soil nutrients and microbial communities. Karst ecosystems are highly fragile, and vegetation degradation has contributed to severe desertification in these regions. However, the specific effects of vegetation disturbance intensity on soil nutrient availability, microbial diversity, and community composition remain poorly understood in karst areas. To address this knowledge gap, this study investigates how varying levels of vegetation disturbance influence soil properties, as well as the diversity, composition, and interactions of bacterial, fungal, and protist communities in a karst ecosystem. The study included four vegetation disturbance intensities: natural vegetation restoration (control) and slight, moderate, and extreme disturbance.ResultsThe findings reveal that higher disturbance intensity significantly alters soil nutrient levels, which in turn affects microbial diversity, abundance, community composition, and interspecies interactions. Specifically, increasing vegetation disturbance intensity led to significant declines in soil available nutrients, including nitrate nitrogen (NO₃−), available phosphorus (AP), and available potassium (AK). Both slight and moderate disturbances reduced bacterial richness and Shannon diversity, whereas extreme disturbance decreased fungal Shannon diversity compared to the control. Bacterial abundance under moderate and extreme disturbances was significantly lower than that in the control, whereas fungal abundance was significantly higher under extreme disturbance. Although vegetation disturbance reduced soil available nutrients, co-occurrence network analysis revealed greater network complexity under moderate and extreme disturbances, with bacterial-bacterial interactions predominating, alongside enhanced bacterial-fungal and bacterial-protistan interactions. Actinobacteria, Ascomycota, and Chlorophyta emerged as keystone taxa. Pearson correlation analysis identified NO3−, pH, and soil moisture as primary drivers of microbial abundance and diversity, indicating that higher disturbance intensities reduce bacterial abundance and fungal diversity by limiting soil nutrient availability and moisture. Additionally, community compositions of bacteria, fungi, and protists were significantly correlated with AP and AK.DiscussionThese findings suggest that short-term vegetation recovery following prolonged moderate and extreme disturbances promotes microbial adaptation to nutrient- and moisture-limited conditions through increased microbial interactions, compensating for losses in abundance and diversity. This study provides valuable insights for ecosystem management and soil restoration in degraded karst landscapes.